MENGIDENTIFIKIASI AJARAN, PRAKTIK DAN RITUAL AGAMA ISLAM DI INDONESIA - Ira Novita Sari; Nanda Sekti Prayetno (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2024)
This research aims to identify the teachings, practices, rituals of the Islamic religion and explore the phenomena of syncretism and acculturation that occur between Islamic teachings and local traditions in Indonesia. This research uses library research which is sourced from books and journals related to the discussion. The results of this research show that Islam in Indonesia has gone through a long process since it was first introduced until it became the majority religion in this country. This study focuses on identifying Islamic teachings, practices and rituals in Indonesia which are influenced by various factors, including local culture, history and social interactions. The process of Islam's entry into Indonesia developed through various theories, such as Mecca, Gujarat, Persia and China theories with the main routes of spread being through trade, marriage, da'wah, Sufism, art and politics. The spread of Islam in Indonesia also involved important figures, such as Wali Songo. Apart from that, the phenomenon of syncretism and acculturation that occurs between Islamic teachings and local traditions has enriched the development of this religion, as can be seen in Islamic traditions that combine elements of local culture. Islamic education through Islamic boarding schools and other Islamic educational institutions also plays a major role in the spread of Islam and social progress in Indonesia. Contemporary, Islam in Indonesia continues to develop with the influence of modernization, technology, social media, and the challenges of extremism. Despite this, Islam in Indonesia has become an integral part of national identity and continues to make a significant contribution to Indonesian society and culture. This research provides insight into how Islam is received, practiced and adapted in Indonesia's diverse cultural context.